THE INFLUENCE OF MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP, PUBLIC OWNERSHIP ON EARNINGS MANAGEMENT IN LISTED COMPANIES IN THE TRANSPORTATION AND RETAIL SUBSECTOR IN 2016-2020 - Aulia Hafidz Hawari; Agung Praptapa; Triani Arofah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This research is research that uses a secondary data on Managerial Ownership, Institutional Ownership, Public Ownership, and Earnings Management in the Transportation and Retail Subsector that listed in Indonesia Stock Exchange in 2016-2020. This research takes the title: “The Influence of Managerial Ownership, Institutional Ownership, Public Ownership on Earnings Management in Listed Companies in the Transportation and Retail Subsector in 2016-2020”. The sample of this research was 14 companies which were obtained by purposive sampling technique. The research data is secondary data with documentation data collection from the Indonesia Stock Exchange and tested using multiple linear regression. The result of this research showing that the variable of Managerial Ownership, Institutional Ownership, and Institutional Ownership have no influence on Earnings Management.